Decrease in diversity and shift in composition of the soil bacterial community were closely related to high available phosphorus in agricultural Fluvisols of North China. (3rd October 2019) - Liu, Chenxu; Zhao, Xiaorong; Lin, Qimei; Li, Guitong
ABSTRACT: Our objectives were to investigate whether AP affects the soil bacterial community composition and diversity in high-level available phosphorus (AP) soils. The bacterial community was analysed through high-throughput sequencing using the Illumina MiSeq platform. Fifteen soils, including barren land, cropland and greenhouse soils which were sandy loam Fluvisols, were selected from different fields in Beijing, China, with AP contents ranging from 5.03 to 391.45 mg kg −1 . Statistical analyses revealed high AP (>100 mg kg −1 ) decreased alpha diversity (Shannon's index, H ') but not beta diversity of the soil bacterial community. The sequencing of 16S rRNA genes showed that Proteobacteria, Bacteroidetes and Acidobacteria were the dominant phyla in sandy loam Fluvisols. AP, soil organic carbon (SOC) and total nitrogen (TN) had synergistic influence on the shift of the bacterial community composition. Moreover, AP was the main driving factor affecting the soil bacterial community composition compared with other environmental factors. The members of the Proteobacteria, Bacteroidetes and Actinobacteria belonging to copiotrophic taxa typically increased in relative abundance in high-P soils, while oligotrophic taxa (mainly Acidobacteria) decreased in relative abundance. Our results demonstrated that the bacterial community composition would shift from oligotrophic to copiotrophic with increasing levels of AP.